2023
DOI: 10.1007/s12144-023-05005-1
|View full text |Cite
|
Sign up to set email alerts
|

Epistemic virtue in higher education: testing the mechanisms of intellectual character development

Abstract: Epistemic virtues are character traits conducive to principled ways of thinking, leading to a life of flourishing. Recent years have witnessed an emergence of theoretical accounts describing how they develop. However, few if any studies have conducted rigorous empirical investigation into the mechanisms of intellectual virtue development. In this study, we review several significant frameworks before utilizing a randomized, pretest/posttest control trial design to understand the impacts of a novel thinking dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…To foster or inculcate epistemic virtues at the individual level, various strategies have been proposed for implementation in higher education (Kuntz and Taylor, 2021). For example, Orona et al have reported experimental successes in enhancing virtue learning among undergraduates (Orona, 2021; Orona and Pritchard, 2022; Orona et al, 2023). In an issue of Education Psychologist on “Educational responses to a ‘post-truth’ world: Diverse approaches to improving thinking about scientific issues,” the education sector’s responses to epistemic deficiency are elaborately discussed (Barzilai and Chinn, 2020).…”
Section: Improving Epistemic Virtues and Addressing Epistemic Vices I...mentioning
confidence: 99%
“…To foster or inculcate epistemic virtues at the individual level, various strategies have been proposed for implementation in higher education (Kuntz and Taylor, 2021). For example, Orona et al have reported experimental successes in enhancing virtue learning among undergraduates (Orona, 2021; Orona and Pritchard, 2022; Orona et al, 2023). In an issue of Education Psychologist on “Educational responses to a ‘post-truth’ world: Diverse approaches to improving thinking about scientific issues,” the education sector’s responses to epistemic deficiency are elaborately discussed (Barzilai and Chinn, 2020).…”
Section: Improving Epistemic Virtues and Addressing Epistemic Vices I...mentioning
confidence: 99%